ANALISIS PENGARUH MANAJEMEN LABA TERHADAP PROFITABILITAS PERUSAHAAN DENGAN GOOD CORPORATE GOVERNANCE SEBAGAI VARIABEL MODERASI: STUDI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2010-2012 - Hasan Salim (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2015)
The aims of this study is to analyze the effect of earning management on the profitability of the company moderated by good corporate governance. The measurement method of earning management employed is discretionary revenue approach that applies the method of conditional revenue developed by Stubben (2010). Good corporate governance is measured by frequency of audit committee meetings. Company’s profitability is measured by using Return on Assets ratio (ROA). The total sample for this study are 70 manufacturing firms listed in Indonesia Stock Exchange from 2010-2012. The method used for data analysis is multiple regression. The result of this study shows that earning management influences company’s profitability. Moreover, good corporate governance is the moderator of the relationship between earning management and company’s profitability.